Relationship between psychological resilience, cognitive flexibility and post-traumatic growth level in patients with severe sepsis treated by continuous renal replacement therapy - Zhao, Changzheng; Zhou, Lancai; Gao, Haixia; Lu, Yongzan; Shi, MiaoMiao (Frontiers in Public Health, 2025)
ObjectiveContinuous renal replacement therapy (CRRT) is the primary treatment for severe sepsis and has been shown to reduce patient mortality. Patients with severe sepsis who receive CRRT frequently experience significant physical and psychological distress, manifesting as shame, social withdrawal, and abnormal cognitive moods. This study aimed to explore the relationship between psychological resilience, cognitive flexibility, and post-traumatic growth (PTG) levels in patients with severe sepsis treated with CRRT.MethodsFrom January to October 2024, patients with severe sepsis who were treated with CRRT in our hospital were selected by convenience sampling as the research object. The Connor-Davidson Resilience Scale (CDRISC), Cognitive Flexibility Scale, and Post-Traumatic Growth Inventory (PTGI) were used to evaluate patients’ psychological resilience, cognitive flexibility, and PTG levels. Statistical methods included the independent sample t test, Pearson analysis, and linear regression analysis.ResultsThe total scores of CDRISC, cognitive flexibility scale and PTGI in 205 patients was (42.98 ± 6.13), (95.04 ± 17.98) and (49.77 ± 9.92), respectively. There was a significant positive correlation between psychological resilience, cognitive flexibility, and PTG levels in patients with severe sepsis treated with CRRT (p < 0.05). Psychological resilience and cognitive flexibility had positive predictive effects on PTG, and there were significant positive predictive effects between psychological resilience and cognitive flexibility (p < 0.05). Psychological resilience directly and positively predicted PTG (β = 0.538, p < 0.05). The indirect effect of psychological resilience on cognitive flexibility was significant (β = 0.677, p < 0.05), and the indirect effect of cognitive flexibility on PTG was significant (β = 0.165, p < 0.05). The chain-mediating effect between psychological resilience, cognitive flexibility, and PTG was significant (β = 0.112, p < 0.05).ConclusionPsychological resilience can affect the PTG level of patients with severe sepsis treated with CRRT and can also indirectly affect PTG levels through direct chain mediation of cognitive flexibility. Targeted intervention strategies should be formulated to improve mental health and promote clinical prognosis.